Middle Triassic transcontinental connection between the North China Craton and the Paleo-Tethys Ocean - Heng Peng; Lin Ding; Chiyang Liu; Massimiliano Zattin; Jianqiang Wang; Licheng Wang (Communications Earth & Environment)
Abstract Middle Triassic paleogeography is essential for the paleoclimate change and ecosystem recovery after the end-Permian mass extinction, but is highly debated in the Paleo-Tethys Ocean and North China Craton, eastern Pangaea. Here we report a detailed provenance fingerprinting dataset from Middle Triassic sediments across the North China Craton, Qinling and Songpan-Ganzi and identify the paleo-uplift in the northern North China Craton as a primary sediment source. We propose that a Middle Triassic transcontinental drainage system flowed from the northern North China Craton through the central Qinling into the eastern Paleo-Tethys Ocean along the gradually descending landform, challenging the suggestion that the North China Craton was a great endorheic basin. The finding of this study will provide a better understanding of Middle Triassic physiography and paleogeography of the North China Craton. Such heterogeneous paleotopography and transcontinental drainage played a critical role in the marine-terrestrial ecosystems of the eastern Pangaea.